Work Efficiency Improvement in the Bidding Process - Diana F. Kelasworoningrum; Moses Laksono Singgih (Institut Teknologi Sepuluh Nopember, 2020)
A higher of competition level requires each company to increase its competitive advantage to be a market leader. One of the options to improve the competitive advantage is to increase company performance efficiency since using this option, operational cost can be reduced. In this particular study, Lean Service concept is applied to eliminate waste that occurs throughout the value stream of bidding process in order to improve procurement performance in terms of its efficiency in PT XYZ. Lean concept implementation started from creating the Value Stream Mapping (VSM) to map current value stream along the bidding process continued with Process Activity Mapping (PAM) to classify waste that occurs throughout the value stream, Borda Count Method (BCM) to determine the critical waste and Root Cause Analysis (RCA) to find the root cause with risk analysis approach which can be used as a reference to determine priority of improvement. The goal of this study is work efficiency improvement in the bidding process by identifying its waste and its root cause since by recognizing those waste, improvement plan can be formulated. This study generates recommendations for improvement plan namely designing SOP which not only standardize its processes moreover set its time limit and improvement in the management system by increasing coordination with end user as well as upgrading procurement knowledge. Those result might be utilized by organization to increase procurement’s work efficiency.